Training students to become responsive therapists: implications from a sequential mixed-methods study on situations that therapists find challenging - Signe Hjelen Stige; Marion Hernes Torrissen; Yngvild Sørebø Danielsen; Reidar Jakobsen; Katharina Teresa Enehaug Morken; Ingrid Dundas (BMC Medical Education, 2024)
Abstract Objective To draw implications for training of therapist responsiveness from a sequential mixed-methods study on challenging clinical situations. Method Study 1: online survey mapping frequency and perceived difficulty of 15 clinical situations in a representative sample of psychologists. Study 2: online survey mapping frequency and perceived difficulty of 19 clinical situations among therapists in child and adolescent psychiatry. Study 3: focus group study exploring the situations identified through study 1 and 2. Results Study 1 and 2 showed that ratings of each situation varied between individuals and context. Study 3 showed that the degree to which a situation was challenging was described as depending on the characteristics of the therapist and the context. Experientially, challenging situations were characterized by lacking access to necessary information, falling short, and disturbing arousal. Perceiving therapeutic opportunities despite the challenging nature of the situation, collegial support, self-knowledge, and engagement were important resources. Conclusion Six implications of the results from the three studies for training of responsiveness are discussed: (1) building self-awareness and conceptualization skills; (2) personalizing training; (3) transforming disturbing arousal into engagement; (4) being exposed to a broad range of clinical situations; (5) training on commonly encountered situations; and (6) building tolerance for uncertainty and capacity to seek support.